2004
DOI: 10.1152/ajpheart.00049.2004
|View full text |Cite
|
Sign up to set email alerts
|

Depressed cardiac tension cost in experimental diabetes is due to altered myosin heavy chain isoform expression

Abstract: Rundell, Veronica L. M., David L. Geenen, Peter M. Buttrick, and Pieter P. de Tombe. Depressed cardiac tension cost in experimental diabetes is due to altered myosin heavy chain isoform expression. Am J Physiol Heart Circ Physiol 287: H408 -H413, 2004. First published March 4, 2004 10.1152/ajpheart.00049.2004.-Cardiac disease in diabetes presents as impaired left ventricular contraction and relaxation; however, the mechanisms underlying contractile protein dysfunction during the progression of disease are unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 27 publications
6
47
3
Order By: Relevance
“…2). We have recently demonstrated that increased ␤-MHC content in rat myocardium correlates with reduced tension cost (35,36). Therefore, the depression of F max and tension cost seen in the late HF group could be due merely to altered isomyosin composition.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…2). We have recently demonstrated that increased ␤-MHC content in rat myocardium correlates with reduced tension cost (35,36). Therefore, the depression of F max and tension cost seen in the late HF group could be due merely to altered isomyosin composition.…”
Section: Resultsmentioning
confidence: 97%
“…A new finding in the present study is the reduction in cross-bridge cycling rate that accompanied the depression of myofilament force development at end-stage HF. It is well established that ␤-myosin is associated with a reduction in cross-bridge cycling (35,36). Therefore, reduced cross-bridge cycling may merely have been the result of altered isomyosin composition in HF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Myosin heavy chain (MyHC) isoforms in the LV myocardium were separated on SDS-polyacrylamide gel electrophoresis according to the method of Rundell et al (2004). We applied an equal amount of protein in each lane (10 g/lane).…”
Section: Effects Of Celecoxib and Dm-celecoxib On Dcm Micementioning
confidence: 99%